Conductive carbon nanotube-reinforced polymer composites and their characterization; IEEE Transactions on Dielectrics and Electrical Insulation; Vol. 23, iss. 3 - Lebedev S. M. Sergey Mikhailovich; Gefle O. S. Olga Semenovna; Amitov E. T. Ernar Tanirbergenuly; Iljin E. S. Evgeny Semenovich; Bezrodny A. E. Alexander Evgenievich; Predtechensky M. R. Mikhail Rudolfovich (2016, 2016)
Title screen